Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1111/j.0742-2822.2004.04013.x
|View full text |Cite
|
Sign up to set email alerts
|

Patent Ductus Arteriosus Complicated by Pulmonary Artery Endarteritis in an Adult

Abstract: patent ductus arteriosus, infective endocarditis, congenital heart disease, transthoracic echocardiographyA 25-year-old man with a history of "childhood murmur" was admitted to our institution Figure 1. Transthoracic echocardiogram, parasternal short axis view at cardiac base (Zoom on main pulmonary artery). A high-velocity jet (PDA) is seen directed from the inferior aspect of the MPA (I indicated with arrow) just above the pulmonary bifurcation. The jet flows superiorly to the mass (indicated with arrow) res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…According to our literature review (Table ), the typical presentation of a PDA‐IE is characterized by prolonged fever (for weeks or even months), sometimes associated to clinical signs of an hemodynamic relevant PDA (fatigue, heart failure, anorexia) or of complications of a PDA‐IE such as septic pulmonary or systemic embolisms. Most case reports include patients with an isolated PDA, not associated with other types of CHD or previous cardiac surgery, except one case, where the PDA‐IE involves the pulmonary valve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our literature review (Table ), the typical presentation of a PDA‐IE is characterized by prolonged fever (for weeks or even months), sometimes associated to clinical signs of an hemodynamic relevant PDA (fatigue, heart failure, anorexia) or of complications of a PDA‐IE such as septic pulmonary or systemic embolisms. Most case reports include patients with an isolated PDA, not associated with other types of CHD or previous cardiac surgery, except one case, where the PDA‐IE involves the pulmonary valve.…”
Section: Discussionmentioning
confidence: 99%
“…The ductus arteriosus Botalli connects the descending aortic arch with the roof of the main and left pulmonary artery and serves as an obligatory right‐to‐left shunt during fetal life. Since first successful surgical ligation of a patent ductus arteriosus (PDA) in 1938 and the establishment of medical and interventional techniques for PDA closure, infective endarteritis in patients with a PDA is a rare or even disappearing clinical entity in developed countries and only described in cases reports and one retrospective study with vegetations related to hemodynamic relevant or less relevant PDA found either in postmortem studies or echocardiographic evaluations. However, in developing countries a PDA remains a predisposing risk factor for IE …”
Section: Introductionmentioning
confidence: 99%
“…On parasternal short-axis and pulmonary long-axis views, color Doppler imaging showed a high velocity, turbulent flow emerging from the descending aorta toward the pulmonary artery (PA) at the level of its bifurcation, and two-dimensional imaging demonstrated multiple, small echo-dense masses in the path of this turbulent jet of blood passing through the PDA to the PA ( Fig. 1, and movie clips [3][4][5]. No other vegetation was seen on the tricuspid and pulmonary valves, and no abscess was identified on aortic annulus.…”
Section: Case Reportmentioning
confidence: 99%
“…2 Patent ductus arteriosus (PDA), even if small, is also associated with a high risk of infective endarteritis (IEa) relative to the normal heart. [3][4][5] IE is rarely seen in pregnancy and puerperal period. It generally occurs in patients with pre-existing heart disease or intravenous (IV) drug abuse, and is associated with very high rates of maternal and fetal loss.…”
mentioning
confidence: 99%
See 1 more Smart Citation